2016
DOI: 10.1111/inm.12184
|View full text |Cite
|
Sign up to set email alerts
|

Engaging clinicians in motivational interviewing: Comparing online with face‐to‐face post‐training consolidation

Abstract: Motivational interviewing (MI) is an evidence-based intervention that has been widely recommended in clinical settings where consumer behaviour change is a goal of treatment. Training clinicians in MI, as with other translational endeavours, does not always result in changes to clinical practice. The present study compares two post-training approaches to consolidate MI skills following a training workshop. We randomly assigned 63 clinicians working in mental health or drug and alcohol services to receive eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Disease prevention is likely to achieve maximum long-term benefits. This model, which recognizes the significance of engagement, autonomy, and collaboration in facilitating behaviour change, has been promoted in mental health services within the study area by clinical leaders over a number of years (Clancy & Taylor 2016). This model, which recognizes the significance of engagement, autonomy, and collaboration in facilitating behaviour change, has been promoted in mental health services within the study area by clinical leaders over a number of years (Clancy & Taylor 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease prevention is likely to achieve maximum long-term benefits. This model, which recognizes the significance of engagement, autonomy, and collaboration in facilitating behaviour change, has been promoted in mental health services within the study area by clinical leaders over a number of years (Clancy & Taylor 2016). This model, which recognizes the significance of engagement, autonomy, and collaboration in facilitating behaviour change, has been promoted in mental health services within the study area by clinical leaders over a number of years (Clancy & Taylor 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A challenge clinicians' face is to influence consumers' beliefs about health behaviours, build motivation, and capacity for lifestyle change within the resource limitations of their environment utilizing client centred approaches such as that outlined in motivational interviewing (Miller & Rollnick 2013). This model, which recognizes the significance of engagement, autonomy, and collaboration in facilitating behaviour change, has been promoted in mental health services within the study area by clinical leaders over a number of years (Clancy & Taylor 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen articles reported changes in knowledge, skills, attitude or behaviour compared to controls, face-to-face, delayed or "attentional" (irrelevant) training. One reported that face-toface learning produced improved learning outcomes compared to online learning, but that this improvement was not significant (Clancy and Taylor, 2016). The difference appeared to be moderated by engagement with the course, with poorer outcomes attributed to online participants accessing fewer training sessions than the face-to-face group.…”
Section: Reported Outcomesmentioning
confidence: 99%
“…Five of these provided written manuals to a control group (Henggeler et al, 2013;Larson et al, 2013;Rawson et al, 2013;Sholomskas & Carroll, 2006;Sholomskas et al, 2005), two of the RCTs studied post-training support and offered no resources to the control group (Carpenter et al, 2012Smith et al 2012, and one study used a delayed training group as a control (Weingardt, Villafranca, & Levin, 2005). Of those studies that were not RCTs, one was a randomised trial comparing face-to-face and online training (Clancy & Taylor, 2016); two were randomised trials comparing different online training formats (Leykin, Cucciare, & Weingardt, 2011;Weingardt, Cucciare, Bellotti, & Lai, 2009); two were prototype, pilot or feasibility studies (Larson et al, 2009;Matejkowski, Dugosh, Clements, & Festinger, 2015); one was a crosssectional survey of substance misuse staff (Aletraris, Shelton, & Roman, 2015); one was a longitudinal study of online learning (Shafer, Rhode, & Chong, 2004), and one was a qualitative study reporting participant experiences of online learning (Curran et al, 2015).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation